Edukasi anti-perundungan sebagai upaya mewujudkan kelas ramah anak di SDN 1 Kota Ternate - Silvani Umar Ali; Samsudin Hi Adam; Syarifah Kurniaty Kahar; Marnia Pangrifat (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2025)
Bullying remains a serious issue in elementary school environments as it negatively affects students’ social and emotional development. This community service program aimed to enhance students’ understanding and attitudes toward anti-bullying through interactive educational activities. The program was conducted at SDN 1 Kota Ternate on July 21, 2025, involving 35 fifth-grade students. The implementation stages included a pre-test, material delivery, interactive discussions, value reinforcement activities, and a post-test evaluation. The evaluation results indicated improvements across all assessed indicators. In recognizing forms of bullying, students in the high understanding category increased from 5 in the pre-test to 23 in the post-test, while the low category decreased from 20 to 4 students. Understanding of bullying impacts also improved, with the high category rising from 5 to 19 students. In terms of response and prevention skills, the high category increased from 4 to 19 students, accompanied by a reduction in the low category from 22 to 6 students. Similar progress was observed in empathy and social awareness, where the high category rose from 6 to 19 students. These findings indicate that participatory anti-bullying education effectively enhances students’ cognitive understanding and fosters positive social attitudes. The program demonstrates strong potential as a sustainable preventive strategy for creating a safe and child-friendly school environment.